On LCD Codes and Lattices - Hou, Xiaolu (2016)
LCD (linear complimentary dual) codes are linear codes that trivially intersect their duals. We address the question of an equivalent concept for lattices. We observe basic properties of the intersection of a lattice with its dual, and consider the construction of lattices from LCD codes using Construction A. Lattices obtained from the intersection of a code with its dual via Construction A are further discussed.